Pengaruh pemberian jus jeruk manis (citrus sinensis.) terhadap nilai VO2 max atlet sepak bola di Gendut Dony Training Camp (GDTC) Salatiga - Andani, Sofia Arum; Widyastuti, Nurmasari (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2017)
Background : Endurance is the ability of the body to perform activities or work for a long time without experiencing fatigue. Based on using of energy systems, endurance is divided into aerobic and anaerobic. Aerobic endurance is measured using VO2max value. Aerobic endurance is supported by the availability of carbohydrates and fats. Intake of carbohydrates as much as 30-60 grams/hour can maintain glucose levels and maintain the level of burning carbohydrates in the body, so it can improve the endurance about 30-60 minutes. Carbohydrate content in 300 ml of sweet orange juice is 54,9 grams that can be used to increase endurance atheletes. Objective : The purpose of this study was to analyze the effect of orange juice on VO2max value in football athletes. Method : This study was in the field of experimental design with post test only with controlled group design. Subject for these study were tweenty-one football athletes which are match with inclusion criteria in Gendut Dony Training Camp (GDTC) Salatiga. The Subject has given 300 ml orange juice and 300 ml placebo 30 minutes before test. VO2max value was measured by using Balke running test. All datas were analyzed by Independent Sample T-tes. Result : Subject characteristic includes age, weight, height, body mass index (BMI), and total food intake were not showing significant difference (p<0,05), therefore subject were categorized as homogen. Significant difference was showed in average of VO2max value between the treatment group (43,67±2,26) and control group (39,33±4,39). Conclusion : Consumption of orange juice 30 minutes before exercising shows a significant impact to increase the VO2max value.